The Ecuadorian Universities and the Work for Sustainability - Espinoza, Galo Arturo Perero; Godinez, Cira Lidia Isaac; Aguirre, Susana DÃƒÂaz; RodrÃƒÂguez, Alfredo Zambrano (International Research Journal of Management, IT & Social Sciences, 2017)
At work a reflection on the environmental management of the Ecuadorian university and prospects of its development from the model of quality of higher education which promotes the Ecuador and the applicable law is addressed. It is intended to address a reflection of the history of the environmental management of Ecuadorian universities, so that they can benefit from the experiences in building a new model to move towards an integrated social and economic interestâs environmental management to ensure the sustainable development.